PROBLEM-SOLVING ABILITY IN THE THINK TALK WRITE LEARNING MODEL ASSISTED BY GEOGEBRA SOFTWARE - Alfira Siti Mutmainah; Yusuf, Yusfita; M. Nuur'aini Sholihat (Program Studi Pendidikan Matematika Universitas Muhammadiyah Kuningan, 2024)
This study was driven by the low mathematical problem-solving abilities of students. To address this issue, Think Talk Write (TTW) learning model, supported by GeoGebra software, was implemented as an intervention. The research aimed to determine whether students taught using the TTW learning model assisted by GeoGebra demonstrate greater improvement in mathematical problem-solving skills compared to those taught through conventional methods. This quasi-experimental study employed a quantitative approach with a non-equivalent control group design. The sampel in this research was class VII-G, with 28 students and Class VII-H, with 26 students. Data were collected using a mathematical problem-solving ability test and analyzed quantitatively. The gain index results indicated that the experimental class experienced a higher improvement in problem-solving skills than the control class. Furthermore, the t' test at a 5% significance level confirmed significant differences in mathematical problem-solving abilities between the two groups. Thus, it can be concluded that the TTW learning model assisted by GeoGebra software significantly enhanced students' mathematical problem-solving abilities compared to conventional learning methods.